2013
DOI: 10.5301/hipint.5000070
|View full text |Cite
|
Sign up to set email alerts
|

MRI evaluation of hip containment and congruency after closed reduction in congenital hip dislocation

Abstract: Dislocated hips showed significantly lower values for all of the evaluated parameters concerning congruency and containment. MRI is not only useful to confirm successful reduction but may also help to predict outcome by evaluating following dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
9
0
4
Order By: Relevance
“…In der vorliegenden Studie wurde das bisher größte Kollektiv kongenitalermittels primärer geschlossener Reposition therapierter und MR-tomografisch nachuntersuchter -Hüftluxationen beschrieben. Bisher vorliegende Studien beinhalten entweder wesentlich geringere Fallzahlen oder nutzen keine MR-Bildgebung zur direkten postinterventionellen Erfolgskontrolle [8,13]. Zudem sind die dort beschriebenen Patientenkollektive bez.…”
Section: Diskussionunclassified
See 3 more Smart Citations
“…In der vorliegenden Studie wurde das bisher größte Kollektiv kongenitalermittels primärer geschlossener Reposition therapierter und MR-tomografisch nachuntersuchter -Hüftluxationen beschrieben. Bisher vorliegende Studien beinhalten entweder wesentlich geringere Fallzahlen oder nutzen keine MR-Bildgebung zur direkten postinterventionellen Erfolgskontrolle [8,13]. Zudem sind die dort beschriebenen Patientenkollektive bez.…”
Section: Diskussionunclassified
“…Die in dieser Studie verwendeten radiologischen Indizes stellen durch ihre hohe Inter-und Intraobserver-Reliabilität über diverse Studien hinweg entscheidende Kriterien für die Erfolgsbewertung der Reposition dar [8,14,15]. Natürlich sind diese Kriterien auch in anderen Kontexten anwendbar, wenngleich dies im klinischen Alltag bei Narkosenotwendigkeit für MR-Untersuchungen bei Säuglingen nur selten der Fall sein wird.…”
Section: Diskussionunclassified
See 2 more Smart Citations
“…[20–24] To children older than 6 months, manipulative reduction and spica cast are used generally. According to the report by Druschel et al, [25] magnetic resonance imaging scanning used to examine the femoral head containment after the close reduction showed that 22 hips were stable and 27 hips were not. For irreducible children who failed in traditional therapy and with poor containment, open reduction is the only way; whereas open reduction has effects of operation trauma and complications, especially femoral avascular necrosis and limited joint mobility.…”
Section: Discussionmentioning
confidence: 99%